Land-Use Practices Affect Water Quality Parameters and Mayfly (Order Ephemeroptera) Assemblage Along River Nzoia (Kenya) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Several river ecosystems are undergoing varied land-use practices, whose monitoring should be continuous. This study evaluated the influence of land-use practices on water quality and macro-invertebrate taxa, specifically the mayfly (order Ephemeroptera) assemblage, along the River Nzoia in Kenya. Four dominant land-use activities were identified as undisturbed, sugarcane growing, settlement, and industrial activities. All the physicochemical water quality parameters displayed significant (P < 0.05) spatial variations. Areas with industrial activities had low DO, as well as high BOD, TA, pH and conductivity, settlement and sugarcane growing areas had high levels of phosphates and nitrates. Land use patterns dictated the macro-invertebrate community structure, where sites with low disturbances had high composition, abundance and diversity and were dominated by order Ephemeroptera, Plecoptera, and Trichoptera (EPT). The distribution of mayfly was significant relative to land-use practice (P < 0.05), where undisturbed sites followed by industrial sites had the highest occurrence and abundance of mayfly taxa, suggesting the occurrence of more tolerant species of mayfly in sites near industrial areas. Dominance of Baetis, and Caenis in undisturbed sites and settlement areas, coupled with Heptagenia and Ephemerella dominance in the sugarcane growing region, but none of the mayfly taxa dominated industrial sites, suggests that they are influenced by anthropogenic activities. PCA plots showed a clear distinction between land-use practices, with ephemeroptera taxa composition being clearly distinguished in the tri-plot. The present study indicates that different types of land-use practices within the study area caused changes in the abundances of the macro-invertebrates and, particularly, mayfly taxa. Thus, all stakeholders should formulate immediate policies that will reduce human impacts on the water quality in River Nzoia. There is also a need to sensitize the local community members to avoid harmful activities along the River Nzoia.